Penafsiran Ayat-Ayat Tentang Angin Menurut Ahmad Musthafa Al-Maraghi - Hasiah, Ahmad Yazid Ali Sati & (Jurnal El-Thawalib, 2020)
Al-Quran in Arabic has an interesting sign system to study. Among the verses of the al-Qur'an which examine the problems of nature, namely about the wind. Apart from being a pleasure to wind, it is also a very big gift given by Allah SWT. to humans. In addition, sometimes the wind can also be a trial / test for humans and can even be a disaster. By explaining the wind in the Koran, the author examines how Allah SWT. give wind to humans. With these problems, the formulation of the problem in this thesis is how Ahmad Mustafa al-Maraghi's interpretation of the verses about the wind will be formulated. The purpose of this research is to find out the interpretation of Ahmad Mustafa al-Maraghi about the verses about the wind.